Ответ:
3*(2х-1)+7=5(х-1)+х+9
6х-3+7=5х-5+х+9
6х-5х-х=-5+9-7+3
0=0
[tex]x€R[/tex]
Объяснение:
[tex]3 \times (2x - 1) + 7 = 5(x - 1) + x + 9 \\ 6x - 3 + 7 = 5(x - 1) + x + 9 \\ 6x - 3 +7 = 5x - 5 + x + 9 \\ 6x + 4 = 5x - 5 + x + 9 \\ 6x + 4 = 6x - 5 + 9 \\ 6x + 4 = 6x + 4 \\ x€R[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
3*(2х-1)+7=5(х-1)+х+9
6х-3+7=5х-5+х+9
6х-5х-х=-5+9-7+3
0=0
Ответ:
[tex]x€R[/tex]
Объяснение:
[tex]3 \times (2x - 1) + 7 = 5(x - 1) + x + 9 \\ 6x - 3 + 7 = 5(x - 1) + x + 9 \\ 6x - 3 +7 = 5x - 5 + x + 9 \\ 6x + 4 = 5x - 5 + x + 9 \\ 6x + 4 = 6x - 5 + 9 \\ 6x + 4 = 6x + 4 \\ x€R[/tex]